Risk Disclosure and Earnings Quality in Indonesia Banking Industries: Fair Value, Diversification, Financial Stability - Javier Reynold Prisadi; Amrie Firmansyah (Riset Akuntansi dan Keuangan Indonesia, 2022)
High earnings quality can reflect a company’s actual performance. Stakeholder needs high earnings quality as earnings information is used for decision-making by stakeholder. This study investigates the effect of fair value, diversification, and financial stability on earnings quality and the roles of risk disclosure in moderating these effects. This study employs secondary data sourced from annual reports available at www.idx.com. The sample used in this study is bank companies from 2016 to 2020. Using purposive sampling, the sample obtained in this study was 180 observations. The research data were analyzed using multiple linear regression for panel data. This study suggested that fair value does not affect earnings quality. Other than that, diversification positively affects earnings quality while financial stability negatively affects earnings quality. Furthermore, risk disclosure failed to moderate the effect of fair value, diversification, and financial stability on earnings quality. This study indicates that the Indonesian Financial Services Authority needs to regulate the bank's diversification and risk disclosure policies. Moreover, the Indonesian Financial Services Authority should maintain and improve the bank’s financial stability policies.